Building trustworthy e-Commerce wesite - Che Hussin, Ab. Razak (2007)
The process of building consumer trust in E-Commerce is based on the presence of trust features or trust attributes in the websites. Consumer may examine e-Commerce websites for the existence of trust attributes. However, to date, which trust attributes contribute to the website’s trustworthiness and which trust attributes give more value to consumer has not been adequately explored. Therefore, the purpose of the paper is to look for the relevant trust attributes for e-Commerce websites and to identify the importance ranking of trust attributes that contribute significantly to the trustworthiness of e-Commerce website. Various journal papers and articles related to e-Commerce field have been referred in order to identify the trust attributes. An online survey that received 1230 respondents was carried out to investigate the importance ranking of ten trust attributes. The paper contributes to the discussion on how to build trust in e-Commerce